TECTONIC EVOLUTION OF THE VOLTRI GROUP AND SESTRI VOLTAGGIO ZONE (SOUTHERN LIMIT OF THE NW ALPS): A REVIEW - Crispini, Laura; Capponi, Giovanni (Ofioliti, 2007)
The present note summarizes the kinematics of the Voltri Group and the Sestri-Voltaggio Zone (Fig. 1) inferred from new structural data. These data have been collected during fieldworks performed by the authors since 1983 up to now in the Voltri Group and the Sestri-Voltaggio Zone. The Voltri Group is a metaophiolitic massif with metasediments (Chiesa et al., 1975), cropping out in central Liguria (Italy). It encompasses several units, re-equilibrated up to different metamorphic P-T peak conditions, which afterwards suffered common deformation and folding. The units of the Voltri Group suffered eclogite to blueschist facies (HP-LT) peak conditions during a subduction event, followed by decompression down to greenschist facies conditions during the exhumation process (Messiga and Scambelluri, 1991; Capponi and Crispini, 1990; Cabella et al., 1994 and references therein). At present, greenschist facies assemblages prevail at a regional scale. The Sestri-Voltaggio Zone occurs at the eastern margin of the Voltri Group and encompasses three units: the Trias-Lias Unit, the Cravasco-Voltaggio Unit and the Monte Figogna Unit (Cortesogno and Haccard, 1984). Also these units were involved in the Alpine subduction-related tectonic events and underwent metamorphic re-equilibration up to different degrees characterized by blueschist facies (Trias-Lias and Cravasco-Voltaggio Units) and pumpellyite-actinolite facies (Monte Figogna Unit) peak metamorphic conditions, later re-equilibrated in lower metamorphic conditions (albitechlorite- epidote mineralogical associations). The tectonic limit between the Voltri Group and the Sestri- Voltaggio Zone is known as the Sestri-Voltaggio Line. Since the end of the last century it drew the attention of the geologists for its peculiar position among units with different metamorphic and structural characteristics. The Sestri- Voltaggio Line played different geodynamic roles in the models proposed by the authors; it was interpreted as a stratigraphic boundary, for example the limit between the “falda delle Pietre Verdi” and the “falda ligure-toscana” by Rovereto (1939), or it was interpreted as a tectonic boundary, for example as a “trasformante” (= transform) fault by Elter and Perusati (1973), a thrust contact in Cortesogno and Haccard (1984) and, more recently, as an extensional fault by Hoogerduijn Strating (1994).